TRADISI PENGOBATAN MAMBANG DEO-DEO DALAM MASYARAKAT MELAYU PANIPAHAN KECAMATAN PASIR LIMAU KAPAS, ROKAN HILIR - Linda, Irma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Trasdition is custom made by a group of people who inherited captivate the generations that and still performed today. Haunter medical tradition deo-deo is a tradition practiced by Malay society Panipahan. Ritual tradition haunter deo-deo treatment is a treatment performed with the magical powers of a psychic, supernatural beings by calling or called by haunter that are thought to cure or treat sisakit. This study aims (1)to determine the implementation process of healing traditions haunter deo-deo in society Malay Panipahan, (2) to know the factors behind the public Malay Panipahan still wearing medical tradition haunter deo-deo,(3)to know the public perception of the medical tradition haunter deo-deo, (4)to know the Islam views haunter medical tradition deo-deo. The method used in this research is descriptive qualitative. Data were obtained from interviews and analyzed in its own language. The study site is Panipahan districts Pasir Limau Kapas, Rokan Hilir. When the study started from the seminar until the Final exam. Data collection techniques used are observation, documentation techniques, interview techniques and engineering literature. The discussion in the research objectives, (1) The background factors are heredity. (2) The process of implementation of the treatment is carried out at night with three nights in a row with the progenitor swing sassy, dance sassy yellow, stabbing fish Terubuk, boyan Dondang, maen sword, dividing member haunter to deliver sassy sea and usher hall sekso, rack and runway seno forestry, maen sword and shower pitcher. (3) The public perception is as connoisseurs of culture. (4) The Islamic view that the treatment haunter deo-deo is shirk because recourse to haunter, Shirk hated God and forgiven by GodKeywords: Tradition, Pangobatan Mambang Deo-Deo